2022
DOI: 10.3390/life12071020
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Angiotensin Serum Levels and Very-Low-Frequency Spectral Power of Heart Rate Variability during Hemodialysis

Abstract: Cardiovascular regulatory mechanisms that fail to compensate for ultrafiltration and cause hypovolemia during hemodialysis (HD) are not completely understood. This includes the interaction between the autonomic nervous system and the biochemistry that regulates blood pressure and modulates cardiac activity and vascular tone in response to hypovolemia in patients treated with HD. The objective was to evaluate the association of spectral indices of heart rate variability (HRV) with serum levels of angiotensin II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…4). Just now Valle-Mandragon del L et al [41] showing that during hemodialysis angiotensin II had a positive correlation with VLF (r=0,390) and with LF/HF (r=0,359) and a negative correlation with LF (r=-0,262) and HF (r=-0,383) bands. Earlier it was reported that low VLF power has been correlated with low levels of testosterone, while other biochemical markers, such as those mediated by the hypothalamic-pituitary-adrenal axis (e.g., cortisol), have not [40].…”
Section: Fig 2 Scatterplot Of Canonical Correlation Between Nitrogeno...mentioning
confidence: 89%
“…4). Just now Valle-Mandragon del L et al [41] showing that during hemodialysis angiotensin II had a positive correlation with VLF (r=0,390) and with LF/HF (r=0,359) and a negative correlation with LF (r=-0,262) and HF (r=-0,383) bands. Earlier it was reported that low VLF power has been correlated with low levels of testosterone, while other biochemical markers, such as those mediated by the hypothalamic-pituitary-adrenal axis (e.g., cortisol), have not [40].…”
Section: Fig 2 Scatterplot Of Canonical Correlation Between Nitrogeno...mentioning
confidence: 89%
“…Authors concluded that although VLF band are influenced by the renin-angiotensin-aldosterone system, they depend primarily on the presence of parasympathetic outflow. However very recently Del Valle-Mandragon L et al [10] showing that during hemodialysis angiotensin II had a positive correlation with VLF band (r=0,390) and with LF/HF (r=0,359) while a negative correlation with LF (r=-0,262) and HF (r=-0,383) bands. Therefore, the contradictions regarding the nature of VLF connections with vagal and sympathetic tone as well as the renin-angiotensin-aldosterone system remain unresolved.…”
Section: Scatterplot Of Canonical Correlation Between Hormonal Variab...mentioning
confidence: 95%
“…Authors concluded that although VLF band are influenced by the renin-angiotensin-aldosterone system, they depend primarily on the presence of parasympathetic outflow. However, del Valle-Mandragon L et al [18] showed that during hemodialysis angiotensin II had a positive correlation with VLF band (r=0.390) and with LF/HF (r=0.359) while a negative correlation with LF (r=-0.262) and HF (r=-0.383) bands. Therefore, the contradictions regarding the nature of VLF connections with vagal and sympathetic tone as well as the renin-angiotensinaldosterone system remain unresolved.…”
Section: Fig 1 Individual Values Of the Discriminant Root Of The Acup...mentioning
confidence: 96%